Blood Pressure Increase in Hypertensive Individuals During Resistance Training Protocols With Equated Work to Rest Ratio - Anderson Caetano Paulo; Anderson Caetano Paulo; Claudia L. M. Forjaz; Décio Mion; Giovanio V. Silva; Silvana Barros; Valmor Tricoli (Frontiers in Physiology, 2020)
Introduction: Despite growing evidence regarding the benefits of resistance training in hypertension, the large and abrupt rise of systolic blood pressure (SBP) observed during resistance exercise execution has resulted in concern about its safety. However, the manipulation of the resistance training protocol (RTP) organization, maintaining the work to rest ratio equated between protocols (W:R-equated), may reduce the SBP increase.Purpose: To compare cardiovascular responses during two W:R-equated RTPs (3 × 15:88 s vs. 9 × 5:22 s – sets × reps: rest between sets) performed in exercises for the lower and upper limbs.Methods: Twelve medicated hypertensives (48 ± 8 years) randomly performed two RTPs in the bilateral leg extension (BLE) and unilateral elbow flexion (UEF) exercises at 50% 1RM. Increases (Δ) of SBP, heart rate (HR) and rate pressure product (RPP) during the exercises were measured by photoplethysmography.Results: In both BLE and UEF exercises, Δ SBP was significantly greater during 3 × 15:88 s than 9 × 5:22 s (peak values: BLE = + 84 ± 39 vs. + 67 ± 20 mm Hg, and UEF = + 46 ± 25 vs. + 37 ± 18 mm Hg, respectively, both p < 0.05). ΔHR and ΔRPP were significantly higher in the 3 × 15:88 s than 9 × 5:22 s in BLE (peak values + 45 ± 17 vs. + 30 ± 8 bpm, and + 15,559 ± 5570 vs. + 10,483 ± 2614 mm Hg. bpm).Conclusion: In medicated hypertensives, a RTP combining more sets with less repetitions per set and shorter rest intervals between sets (i.e., 9 × 5:22 s) produced a smaller increase in cardiovascular load (ΔSBP, ΔHR and ΔRPP) during its execution than a protocol with fewer longer sets (i.e., 3 × 15:88 s).